Analisa Pertanggungjawaban Pidana Direksi dan Komisaris Perusahaan Efek dalam Kasus Insider Trading Pasca Perkembangan Regulasi 2019-2024 - Lizardo, Jimmy; Sambuaga, Eddy; Napitupulu, Diana R.W. (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
Law enforcement against capital market crimes, particularly insider trading, has become increasingly relevant in line with regulatory developments in Indonesia during the 2019–2024 period. This study aims to analyze the forms of criminal liability that can be imposed on directors and commissioners of securities companies in insider trading cases, as well as how current regulations strengthen or change previous legal approaches. This research uses a normative juridical method with a regulatory approach, case studies, and analysis of current legal literature. The results show that post-2019 regulations, including updates to the Capital Market Law and OJK regulations, expand the scope of criminal liability not only to direct perpetrators but also to parties with supervisory and control functions, such as commissioners and directors. It was also found that the principles of strict liability and command responsibility are beginning to be accommodated in capital market law enforcement practices. In conclusion, increased standards of corporate compliance and transparency require an active role from directors and commissioners, while also opening up the possibility of criminal liability in the event of negligence or involvement in insider trading practices.